Exclusion-Proneness in Borderline Personality Disorder Inpatients Impairs Alliance in Mentalization-Based Group Therapy - Euler, Sebastian; Wrege, Johannes; Busmann, Mareike; Lindenmeyer, Hannah J.; Sollberger, Daniel; Lang, Undine E.; Gaab, Jens; Walter, Marc (Frontiers in Psychology, 2018)
Interpersonal sensitivity, particularly threat of potential exclusion, is a critical condition in borderline personality disorder (BPD) which impairs patients’ social adjustment. Current evidence-based treatments include group components, such as mentalization-based group therapy (MBT-G), in order to improve interpersonal functioning. These treatments additionally focus on the therapeutic alliance since it was discovered to be a robust predictor of treatment outcome. However, alliance is a multidimensional factor of group therapy, which includes the fellow patients, and may thus be negatively affected by the exclusion-proneness of BPD patients. The aim of this pilot study was to examine the predictive value of threat of social exclusion for the therapeutic alliance in MBT-G. In the first part of the study, social exclusion was experimentally induced in 23 BPD inpatients and 28 healthy subjects using the Cyberball paradigm, a virtual ball tossing game. The evoked level of threat was measured with the Need-Threat Scale (NTS) which captures four dimensions of fundamental human needs, i. e. the need for belongingness, for self-esteem, for control, and for a meaningful existence. In the second part of the study, therapeutic alliance was measured on three dimensions, the therapists, the fellow patients and the group as a whole, using the Group-Questionnaire (GQ-D). BPD patients scored higher in their level of threat according to the NTS in both, the inclusion and the exclusion condition. The level of threat after exclusion predicted impairments of the therapeutic alliance in MBT-G. It was associated with more negative relationships, lower positive bonding and a lower positive working alliance with the fellow patients and lower positive bonding to the group as a whole whilst no negative prediction of the alliance to the therapists was found. Consequently, our translational study design has shown that Cyberball is an appropriate tool to use as an approach for clinical questions. We further conclude that exclusion-proneness in BPD is a critical feature with respect to alliance in group treatments. In order to neutralize BPD patients’ exclusion bias, therapists may be advised to provide an “inclusive stance”, especially in initial sessions. It is also recommendable to strengthen patient to patient relations.